Pengembangan Sistem Informasi MA Zainul Anwar Kraksaan Berbasis Web dengan Sistem Multi User Manejemen - Tholib, Abu; Marzuki, Muhammad Ismail; Tsabbit Albannani, Nur Wahyu; Ihsan, Gilang Hafidzul; Salman, Moh (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
The lack of effective information dissemination methods at MA Zainul Anwar Kraksaan has hindered the community and parents' understanding of school programs. This research aims to develop a web-based information system featuring multi-user management to address these challenges. Using the Research and Development (R&D) approach with the Waterfall model, the study involved stages of need analysis, system design, implementation, testing, and maintenance. Data were collected through observations and interviews, and the findings were used to design a user-friendly system tailored to the school’s needs. The results demonstrate that the developed system significantly improves communication efficiency and transparency, streamlines administrative processes, and provides a robust information portal. The study recommends adopting similar systems in other schools facing comparable challenges to enhance communication and operational efficiency.